Agriculture and Achieving the Millennium Development Goals - World Bank (Washington, DC, 2012)
Given that the majority of poor people live in rural areas or rely on agriculture, and that agriculture paves the way for economic growth in the poorer nations, agricultural and rural development will underlie progress on the broad array of economic and social indicators emphasized by the Millennium Development Goals (MDGs). The most effective strategy for making steady, sustainable progress toward the MDGs is to serve all the goals in an integrated way. While the agricultural sector provides critical inputs for attaining the MDG targets, the broad improvements in human capital needed to reach those targets will also result in a considerably more productive and resilient agricultural sector. There is a need to undertake a critical review of the pathways by which agriculture can contribute directly or indirectly to attaining the MDGs. This report centers on the first MDG, concerned with eradicating extreme poverty and hunger, but looks at the direct and indirect links between the MDGs and agriculture. Following an explanation of the MDGs and a discussion of their progress to date, the potential contributions of agriculture to achieving the MDGs are assessed goal by goal in the second chapter. The third chapter examines more closely how the targets of MDG 1 can be achieved in Sub-Saharan Africa (Ethiopia and Zambia), and how agricultural and economic growth, together with larger investments in social sectors including health and education, can substantially narrow the gap between business-as usual and MDG outcomes for Target 2 of MDG 1, halving child malnutrition levels. This report then examines how trade and macroeconomic policies for agriculture can improve the attainment of the MDGs, particularly the goal of halving poverty. The final section sets out some conclusions.